Dual therapy with clopidogrel and rivaroxaban in cats with thromboembolic disease. Issue 4 (April 2022) - Lo, Sara T; Walker, Ashley L; Georges, Catherine J; Li, Ronald HL; Stern, Joshua A
Objectives: Feline arterial thromboembolism (ATE), an often devastating outcome, was recently shown to affect 11.3% of cats with hypertrophic cardiomyopathy over 10 years. Current American College of Veterinary Internal Medicine guidelines recommend the use of clopidogrel in cats at risk for ATE, with addition of a factor Xa inhibitor in very high risk or post-ATE cases. To date, no studies have examined the safety or efficacy of this combined antithrombotic therapy. This retrospective case series aimed to assess the frequency and type of adverse events that occurred in cats prescribed dual clopidogrel and rivaroxaban therapy. Secondary aims were to evaluate indications for dual therapy and clinical outcome. Methods: The study included 32 cats prescribed clopidogrel (18.75 mg PO q24h) and rivaroxaban (2.5 mg PO q24h) on an outpatient basis over a 5-year period. Results: Cats were prescribed dual therapy for at least one of the following: ATE event (n = 18), presence of an intracardiac thrombi (n = 17) or presence of spontaneous echocardiographic contrast (SEC) (n = 16). Five cats experienced adverse effects that could be attributed to medications, a median of 13 days from initiation (epistaxis, hematemesis, hematochezia or hematuria). No cat required hospitalization as a result of these events. Median survival time from onset of therapy was 257 days (interquartile range [IQR] = 38–497) for all cats, 502 days (IQR = 171–663) for ATE cats, 725 days (IQR = 133–856) for cats with an ATE to two or more limbs and 301 days (IQR = 221–431) for cats with only one limb affected. Recurrence rate of ATE while on dual therapy was 16.7%; no cat newly developed an ATE while on dual therapy. Conclusions and relevance: Dual antithrombotic therapy with clopidogrel and rivaroxaban resulted in a low reported incidence of adverse events. Cats placed on dual therapy for an ATE event experienced a low rate of recurrence and effective thromboprophylaxis was achieved in cats with intracardiac thrombi or SEC.